Relative scapular-muscle ratios during maximal isokinetic shoulder-girdle strength performance in elite field hockey players - Vanderstukken, F.; Borms, D.; Berckmans, K.; Spanhove, V.; Cools, A.-M. (Journal of Athletic Training, 2020)
Context: The shoulder joint and girdle are highly loaded during field hockey play. To optimize performance and to better substantiate preventive programs, it is important to gain insight into shoulder-girdle muscle function and balance in this athlete population. Objective: To evaluate relative scapular muscle-activity ratios through surface electromyography during maximal isokinetic strength testing in elite male field hockey players compared with nonathletes. Design: Cross-sectional study. Setting: Institutional laboratory. Patients or Other Participants: Twenty-five elite field hockey players from the Belgian National Team and 25 age- and sex-matched nonathletes. Intervention(s): We measured bilateral activity in 4 scapular muscles (upper trapezius [UT], middle trapezius [MT], lower trapezius [LT], and serratus anterior [SA]) during an external-internal rotation and protraction-retraction isokinetic shoulder protocol. Main Outcome Measure(s): Relative scapular muscle-activity ratios, or balance ratios, of the UT:MT, UT:LT, UT:SA, SA:MT, and SA:LT. Results: We noted lower ratios bilaterally in the athlete group compared with the control group for the UT:MT, UT:LT, and SA:MT ratios during protraction, retraction, and external rotation, respectively, and unilaterally (dominant side only) for the UT:LT ratio during protraction. No consistent trend was present for established side differences in the studied balance ratios. Conclusions: Compared with nonathletes, elite field hockey players had altered intramuscular (within the trapezius) and intermuscular (between the trapezius and SA) balance ratios during maximal shoulder-girdle contractions, with relatively more MT and LT activity. This may reflect a sport-specific adaptation to optimize coordinated activity of the scapulothoracic muscles, meeting the specific demands of field hockey movements and simultaneously better protecting the shoulder against injury. Our results can assist in optimizing high-performance training and in supporting injury-prevention programs, which are key to both successful and long-lasting athletic careers.